Profil Daya Tahan Jantung Paru Pada Atlet Pra Pon Sulut Cabang Olahraga Futsal Putra Tahun 2023 - Igo Ariyanto Ginoga; Fentje W. Langitan; Maxi M.L. Moleong (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
This study aims to determine the profile of cardiorespiratory endurance among male futsal athletes participating in Pra PON SULUT 2023, as well as to analyze the variability in their cardiovascular performance. The research employs a descriptive quantitative approach, involving 35 athletes selected through total sampling. Measurements were conducted using the bleep test to assess cardiorespiratory endurance. The results indicate that 75% of the athletes fall within the "good" to "very good" categories, while the remaining athletes are classified from "adequate" to "poor." These findings suggest that the majority of the athletes have achieved optimal levels of endurance; however, significant individual differences exist, likely influenced by initial physical condition and training intensity. The results of this study align with the theories of Depdiknas (2010) and Pekik (2004), which emphasize the importance of respiratory and circulatory efficiency in supporting athletic performance, and support Husein Argasmita’s (2007) view that the variability in cardiorespiratory endurance requires special attention in athlete development. This study is expected to serve as a basis for designing more focused and individualized training programs to enhance the performance of futsal athletes in future competitions.